Evaluation of value-added agricultural advisory services: Case study of agriclinics in Southern India - Glendenning, Claire J.; Asenso-Okyere, Kwadwo; Babu, Suresh Chandra (International Food Policy Research Institute, 2011)
Introduction of private enterprises to deliver agricultural advisory services is seen as a strategy to increase the coverage and effectiveness of the pluralistic extension system in developing countries. The Indian national program of agriclinics and agribusiness centers, started in 2002, aims to provide farmers with a reliable alternative to the private input dealer by subsidizing technically trained agricultural graduates to establish their own agricultural input shops and agriclinic laboratories. In 2008, Tamil Nadu state began its own version of the program, called Agriclinics cum Mini Soil Testing Laboratories, which provides subsidized funding to establish soil testing laboratories by primary agricultural cooperative banks (PACBs) or independent agricultural graduates.